2014
DOI: 10.4300/jgme-d-13-00241.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Protected Sleep Period for Internal Medicine Interns on Overnight Call on Depression, Burnout, and Empathy

Abstract: Background Patient safety and sleep experts advocate a protected sleep period for residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 23 publications
2
32
0
10
Order By: Relevance
“…Many causes of burnout derive from organizational-and system-level factors, including electronic health records (EHRs (5), 33,47,52,54,57 Canada (2), 42,48 Egypt (1), 53 and multinational (2). 24,35 Study designs included randomized controlled trials (10), 23,28,29,37,39,40,42,45,48,51 prospective studies (5), 43,44,50,56,60 cross-sectional studies (7), 19,38,47,52,53,66,68 and other designs (4). 24,27,35,59 The included studies evaluated interventions among primary care physicians and residents (12) 31,63,66 and groups of physicians with specialty unspecified (7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many causes of burnout derive from organizational-and system-level factors, including electronic health records (EHRs (5), 33,47,52,54,57 Canada (2), 42,48 Egypt (1), 53 and multinational (2). 24,35 Study designs included randomized controlled trials (10), 23,28,29,37,39,40,42,45,48,51 prospective studies (5), 43,44,50,56,60 cross-sectional studies (7), 19,38,47,52,53,66,68 and other designs (4). 24,27,35,59 The included studies evaluated interventions among primary care physicians and residents (12) 31,63,66 and groups of physicians with specialty unspecified (7).…”
Section: Resultsmentioning
confidence: 99%
“…47 On the other hand, interns randomized to receive 5 hours of protected time to sleep while on call reported significantly lower levels of MBI-assessed emotional exhaustion and MBI-assessed depersonalization over 6 consecutive 4-week periods. 51 Similarly, surveys of junior doctors found that after 6 months of WTR compliance, those working schedules that required 7 consecutive nights experienced a greater accumulation of fatigue when compared with those limited to working just 3 or 4 nights in row. 52 A time-banking intervention for medical school faculty found that institutional recognition of time spent on additional activities, such as teaching, clinical service, and mentorship, improved job satisfaction (P¼.02).…”
Section: Teamworkmentioning
confidence: 99%
“…9,10 For 3 high-quality RCTs, as judged by the Jadad scale, protected sleep periods 18 and communication and stress management 8 had no effect on burnout rates. Self-care workshops resulted in a decrease in the depersonalization component of burnout.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 observational studies that were assessed using the NOS (provided as online supplemental material), 2 were rated high quality, 12,13 and 7 were rated as being of moderate quality. 3,9,14,15,17,21,24 Of the 5 RCTs that were assessed using the Jadad scale (TABLE 1), 3 were rated high quality 8,18,19 (score ! 3), and the remaining 2 were rated to be of moderate quality.…”
Section: Resultsmentioning
confidence: 99%
“…Sin embargo, se han reportado diversos problemas en el internado que podrían dificultar el aprendizaje y la realización de procedimientos por parte del interno, como sobrecarga laboral (7,8) , gran cantidad de trabajo administrativo (papeleo) (9,10) , inadecuada docencia, falta de supervisión de los procedimientos realizados (2) , falta de oportunidades para realizar ciertos procedimientos (11) , entre otros.…”
Section: Introductionunclassified